Azasugar inhibitors as pharmacological chaperones for Krabbe disease12. Issue 5 (20th May 2015) - Hill, Chris H.; Viuff, Agnete H.; Spratley, Samantha J.; Salamone, Stéphane; Christensen, Stig H.; Read, Randy J.; Moriarty, Nigel W.; Jensen, Henrik H.; Deane, Janet E.
<x xml:space="preserve">Abstract</x> Modified azasugar molecules have been synthesized and characterized as excellent pharmacological chaperone candidates to treat the neurodegenerative disorder Krabbe disease.